(untitled) (Research, Society and Development, 2022)
Objective: Evaluate the association between eating habits and sociodemographic factors in adults with Type 1 Diabetes Mellitus (T1DM) during COVID-19’s social distancing. Design: Transversal, descriptive and analytical study carried out in July 2020, using a form on the platform Google Forms®. Sociodemographic data, information on social distancing and food choices were collected. For statistical analysis it was performed the Chi-Square Test, considering p<0.05. Results: There was an association between social distancing and being female (p=0.014), living with individuals with diabetes (p=0.037) and having income maintained during the pandemic (p=0.032). Being female was associated with increased consumption of snacks (p=0.003) and sweets (p=0.016). Being between 18 and 24 years old was associated with changing food consumption (p=0.001), increasing consumption (p=0.001), especially snacks (p=0.005). Being over 45 years old was associated with maintaining the eating pattern (p=0.001). Having income maintained or increased was associated with maintaining the eating pattern (p=0.042). Conclusion: Age, gender and income can influence the eating habits of adults with T1DM during social distancing, which alerts to the need to maintain nutritional assistance in order to ensure a healthy eating pattern, as well as to have minimum income guarantee programs to ensure access to good quality food.